Construction of a Large Size Human Immunoglobulin Heavy Chain Variable (VH) Domain Library, Isolation and Characterization of Novel Human Antibody VH Domains Targeting PD-L1 and CD22 - Sun, Zehua; Li, Wei; Mellors, John W.; Orentas, Rimas; Dimitrov, Dimiter S. (Frontiers in Immunology, 2022)
Phage display is a well-established technology for in vitro selection of monoclonal antibodies (mAb), and more than 12 antibodies isolated from phage displayed libraries of different formats have been approved for therapy. We have constructed a large size (10^11) human antibody VH domain library based on thermo-stable, aggregation-resistant scaffolds. This diversity was obtained by grafting naturally occurring CDR2s and CDR3s from healthy donors with optimized primers into the VH library. This phage-displayed library was used for bio-panning against various antigens. So far, panels of binders have been isolated against different viral and tumor targets, including the SARS-CoV-2 RBD, HIV-1 ENV protein, mesothelin and FLT3. In the present study, we discuss domain library construction, characterize novel VH binders against human CD22 and PD-L1, and define our design process for antibody domain drug conjugation (DDC) as tumoricidal reagents. Our study provides examples for the potential applications of antibody domains derived from library screens in therapeutics and provides key information for large size human antibody domain library construction.